2018
DOI: 10.4103/aja.aja_77_17
|View full text |Cite
|
Sign up to set email alerts
|

The risk of human papillomavirus infection for male fertility abnormality: a meta-analysis

Abstract: Human papillomavirus (HPV) is the most common sexually transmitted virus in males and females worldwide; yet its impact upon male fertility remains unclear. The objective of this study was to evaluate the potential impact of HPV infection in semen on male fertility abnormality. A systematic literature search was performed in PubMed, Medline, Embase, Web of Science, and the Cochrane Library database for relevant publications up to May 6, 2017. The odds ratio (OR), and its corresponding 95% confidence interval (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…In this regard, many original studies, reviews and meta-analyses reported that HPV semen infection is related to reduced fertility both in natural and assisted conceptions. However, the exact mechanisms responsible for this condition have been never definitely assessed (16,19,31,33,39,44,45). Table 3 reports the main studies which investigated how HPV seminal infection in males may impair reproductive outcome in natural and/or assisted fertility.…”
Section: Hpv Semen Infection and Reproductive Outcomesmentioning
confidence: 99%
“…In this regard, many original studies, reviews and meta-analyses reported that HPV semen infection is related to reduced fertility both in natural and assisted conceptions. However, the exact mechanisms responsible for this condition have been never definitely assessed (16,19,31,33,39,44,45). Table 3 reports the main studies which investigated how HPV seminal infection in males may impair reproductive outcome in natural and/or assisted fertility.…”
Section: Hpv Semen Infection and Reproductive Outcomesmentioning
confidence: 99%
“…Among couples unable to conceive, infertility is to some extent attributable to a male factor in approximately 50% of cases [1, 3,4]. While occupation, environmental and genetic factors are recognized as important causes of male infertility for some time [3], virologic threats by human papillomavirus (HPV) infections have only recently been described [5][6][7]. Indeed, although HPV infection is one of the most common viral infections worldwide, it is almost exclusively linked with pathogenesis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although HPV infection is one of the most common viral infections worldwide, it is almost exclusively linked with pathogenesis of cancer. More recent studies have shown that male and couple subfertility may results from a HPV virion producing infection in one or both of the partners [6][7][8]. Also, the average lifetime probability of acquiring HPV among those with at least 1 opposite sex partner is more than 84.6% for women and 91.3% for men and more than 80% of women and men acquire HPV by age 45 years [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genetic background and reproductive history, environmental factors and current lifestyle habits have been proposed as causes of male and female infertility [9]. According to large systematic reviews and meta-analyses, the lifestyle factors associated with reduced fertility are (1) sexually transmitted diseases, (2) psychological stress, (3) cigarette smoking, (4) alcohol use, (5) nutrition and diet, (6) physical activity and exercise, (7) underweight, (8) overweight and obesity, and (9) environmental pollutants [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Given the situation of one-third of Japanese couples currently or previously worrying about infertility, for those who are trying to conceive or hope to have a child in the future, knowledge about the lifestyle factors associated with reduced fertility may help to prevent infertility.…”
Section: Introductionmentioning
confidence: 99%